2021
DOI: 10.1177/10781552211020798
|View full text |Cite
|
Sign up to set email alerts
|

A real world analysis of first line treatment of advanced EGFR mutated non-small cell lung cancer: A multi-center, retrospective study

Abstract: Introduction The recently published FLAURA trial demonstrated that osimertinib has remarkable efficacy in front-line setting for non-small cell lung cancer (NSCLC). While this has transformed current practice, there are no effective treatments following progression on osimertinib. The aim of our study was to compare progression-free survival (PFS) and overall survival (OS) between patients initiated on osimertinib to those started on other EGFR TKIs. Methods This was a multicenter, retrospective study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Among these patients, 2L osimertinib monotherapy was most common (58.3%–60.7%), followed by other EGFR TKIs (28.6%–30.1%), and chemotherapy alone or chemotherapy plus IO therapy (6.0%–7.5%). The frequency of 2L osimertinib is similar to the findings from a recently published retrospective multi‐center study using data from 2014 to 2019 which also reported that osimertinib was the most common 2L treatment option after 1L earlier generation EGFR TKIs, with 65.8% of patients progressing on other EGFR TKI and osimertinib accounting for 55.7% of subsequent treatments 33 . However, the frequencies of 2L osimertinib and chemotherapy contrast with the treatment patterns observed in previously published data reported from clinical trials and real‐world settings; those studies generally reported lower frequencies of 2L osimertinib and higher frequencies of chemotherapy, which may be a reflection of the study periods ending pre‐2018 34,35 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among these patients, 2L osimertinib monotherapy was most common (58.3%–60.7%), followed by other EGFR TKIs (28.6%–30.1%), and chemotherapy alone or chemotherapy plus IO therapy (6.0%–7.5%). The frequency of 2L osimertinib is similar to the findings from a recently published retrospective multi‐center study using data from 2014 to 2019 which also reported that osimertinib was the most common 2L treatment option after 1L earlier generation EGFR TKIs, with 65.8% of patients progressing on other EGFR TKI and osimertinib accounting for 55.7% of subsequent treatments 33 . However, the frequencies of 2L osimertinib and chemotherapy contrast with the treatment patterns observed in previously published data reported from clinical trials and real‐world settings; those studies generally reported lower frequencies of 2L osimertinib and higher frequencies of chemotherapy, which may be a reflection of the study periods ending pre‐2018 34,35 …”
Section: Discussionsupporting
confidence: 86%
“…The frequency of 2L osimertinib is similar to the findings from a recently published retrospective multi-center study using data from 2014 to 2019 which also reported that osimertinib was the most common 2L treatment option after 1L earlier generation EGFR TKIs, with 65.8% of patients progressing on other EGFR TKI and osimertinib accounting for 55.7% of subsequent treatments. 33 However, the frequencies of 2L osimertinib and chemotherapy contrast with the treatment patterns observed in previously published data reported from clinical trials and real-world settings; those studies generally reported lower frequencies of 2L osimertinib and higher frequencies of chemotherapy, which may be a reflection of the study periods ending pre-2018. 34,35 The key strengths of this study include the use of linked large pharmacy and medical claims databases which allow for a comprehensive view of treatment patterns.…”
Section: Discussionmentioning
confidence: 66%
“…While our analysis is the first across the CEE region documenting the clinical outcomes and attrition rates on 1L 1G/2G EGFR TKIs, it brings evidence applicable only to the pre-FLAURA era. The preliminary reports of the first real-world studies with front-line osimertinib in advanced/metastatic EGFRm NSCLC are in line with the improved survival data reported in randomized clinical studies [ 34 , 35 ]. The median rwPFS on 1L 1G/2G EGFR TKIs recorded across the CEE cohort was of 14.0 months, being slightly higher than in the primary REFLECT study, where it was 12.6 months [ 24 ].…”
Section: Discussionmentioning
confidence: 60%
“…The first real-world studies also showed improved results with osimertinib in 1L. For example, in a retrospective analysis (28) including 172 patients with EGFRm NSCLC, the 12-and 18month PFS was greater for osimertinib versus 1G/2G EGFR TKIs (80% and 70% vs. 64% and 39%, respectively, p<0.0036). The first prospective study exploring 1L osimertinib in 126 patients with advanced EGFRm NSCLC in real-life setting (29) showed median PFS of 18.9 months, median time to discontinuation 25.3 months and median OS not reached.…”
Section: Discussionmentioning
confidence: 98%